Effect of inflammation on neurovascular coupling, microperfusion, and clinical outcomes in ischemic stroke patients: a case series report - Cancino, Astrid; Muñoz, Pablo; Cox, Pablo; Acevedo, Lilian; Castillo, Sebastián; Letelier, Aldo; Veloz, Alejandro; Rodriguez-Fernandez, Maria; Chabert, Steren (Frontiers in Medicine, 2025)
IntroductionIschemic stroke leads to a range of sequelae that affect daily functioning. In many cases, such as wake-up strokes or late hospital arrivals, the therapeutic window for reperfusion is missed for the patient, and functional outcomes remain uncertain. The inflammatory response to ischemia plays a pivotal role in the initiation, progression, and recovery phase of stroke. Yet, a gap remains in understanding its impact on neuroimaging and clinical outcomes. This prospective case series investigates the relationship between inflammation, neuroimaging findings in the first 48 h after stroke onset, and 6-months clinical outcomes.MethodsBiomarkers of inflammation, such as C-reactive protein (CRP) and Interleukin 6 (IL-6), as well as oxidative stress (OS), were measured. Additionally, advanced neuroimaging techniques were used to assess neurovascular coupling, cerebrovascular reactivity, and intravoxel incoherent motion (IVIM) for microperfusion. After 6 months, outcomes were evaluated using the modified Rankin Scale (mRS), and participants were categorized into two groups: those with good outcomes (mRS 1–3) and those with poor outcomes (mRS 4–6).ResultsA total of 23 wake-up stroke patients not eligible for reperfusion therapy were included: 11 with cortical ischemic lesions and 12 with subcortical or deep ischemic lesions, involving the thalamus, basal ganglia, brainstem, or cerebellum. Significant differences were observed in pseudodiffusion (D*) and delayed neurovascular coupling between patients with normal and elevated inflammatory markers. CRP levels showed a positive correlation with these imaging findings. Additionally, when stratified by 6-months outcomes, patients with poor recovery had higher CRP levels and altered contralateral cerebrovascular reactivity within the first 48 h of admission.DiscussionThese preliminary findings suggest that combining inflammatory and neuroimaging markers across cortical and subcortical stroke subtypes could enhance understanding of inflammation’s role in early hemodynamic responses and long-term effects outcomes. Further research is needed to explore the broader implications of these case series representations.